2020
DOI: 10.1186/s12866-020-01914-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the effect of vitamin C on growth & biofilm-forming potential of Streptococcus mutans isolated from patients with dental caries

Abstract: Background: Streptococcus mutans is a major cause of dental caries. Its capacity to produce biofilm is fundamental in the pathogenesis of this ubiquitous condition. As maintaining a healthy dentition is a genuine goal given the contemporary advance in caries control, researchers are striving to achieve a breakthrough in caries therapy. We are taking the anti-cariogenic properties of vitamin C a step-further, considering the well-known evidence of the inversely proportionate relationship between salivary levels… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
(44 reference statements)
1
14
1
Order By: Relevance
“…In our investigation, the MIC and MBC of ascorbic acid were 12.5 and 25 mg/ml respectively, against S. mutans, whereas in an earlier study, the average MIC and MBC were 9.38 and 10.16 mg/ml, respectively 34 . These MIC and MBC result variations may be due to the susceptibility pattern of the S. mutans strains used, the purity of ascorbic acid, and the experimental settings carried out in different laboratories.…”
Section: Discussioncontrasting
confidence: 77%
“…In our investigation, the MIC and MBC of ascorbic acid were 12.5 and 25 mg/ml respectively, against S. mutans, whereas in an earlier study, the average MIC and MBC were 9.38 and 10.16 mg/ml, respectively 34 . These MIC and MBC result variations may be due to the susceptibility pattern of the S. mutans strains used, the purity of ascorbic acid, and the experimental settings carried out in different laboratories.…”
Section: Discussioncontrasting
confidence: 77%
“…There was up to a 92% reduction in biofilm production. Likewise, Sendamangalam et al (2011) and Eydou et al (2020) reported 2 mg/ml and 5.61 mg/ml, respectively, as the biofilm inhibitory concentration of vitamin C against S. mutans.…”
Section: Discussionmentioning
confidence: 96%
“…Ascorbic acid, commonly known as Vitamin C, is an essential dietary nutrient that is necessary for a variety of physiological processes in the human body, including wound repair and collagen production [ 27 ]. Ascorbic acid is also an antioxidant [ 28 ] with antibacterial activity [ 29 ], and the ability to disrupt exopolysaccharide biofilm formation in E. coli [ 30 ], S. mutans [ 31 ], B. subtilis [ 32 ], and S. aureus [ 33 ]. Ascorbic acid is a glycation inhibitor [ 25 , 34 ] via its antioxidant activity and ability to ionically bind to proteins, competitively inhibiting the binding of glucose.…”
Section: Discussionmentioning
confidence: 99%